Making exaggerated claim & misleading advertisement: am i wrong? - Md Pauzi, Suria Fadhillah; Mustapha, Musramaini (Universiti Teknologi MARA, Terengganu, 2022)
In Malaysia, the advertising sector is mostly self-regulated and governed by many laws, regulations, standards, and guidelines. The Malaysian Code of Advertising Practice, which governs printed and paidfor- space advertisements, is administered by the Advertising Standards Authority.